STRENGTHENING THE QUALITY OF ISLAMIC RELIGIOUS VALUES IN THE INDONESIAN MUALLAF CENTER (MCIP) ENVIRONMENT, CENTRAL SULAWESI - Pambek, Kumaeni; Ahmad Syahid; Ubadah, Ubadah; S. Abajia, Hasran (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This study examines the cultivation and strengthening of Islamic religious values at the Muallaf Center Indonesia Peduli (MCIP) in Central Sulawesi. The research focuses on three main problems: first, how Islamic religious values are cultivated at the MCIP; second, how the quality of these values is strengthened; and third, what supporting and inhibiting factors influence the cultivation and strengthening of Islamic religious values at the MCIP. The objectives of this study are to understand the methods used to cultivate Islamic religious values at the MCIP, to analyze the strengthening of their quality, and to identify the factors that support or hinder these efforts. The study adopts a qualitative approach with descriptive techniques for presenting data from informants. Data were collected through observation, in-depth interviews, and document analysis. The analysis process involved data reduction, presentation, verification, and conclusion drawing. The findings reveal that the steps taken by the MCIP to cultivate and strengthen Islamic religious values align with established guidance theories. These include teaching, habituation, role modeling, motivation, and rule enforcement. The guidance process for new converts (muallaf) is implemented through structured programs. Furthermore, the study highlights that the implications of these efforts can be observed in the religious behaviors of the participants, which are consistent with Bloom’s taxonomy. Based on the findings, it is recommended that MCIP facilitators maintain the strategies currently used to cultivate and strengthen Islamic religious values. Additionally, they are encouraged to introduce innovative approaches to enhance the quality of guidance provided to new converts, ensuring better outcomes in the future.